Using Simulation to Assess Nurse Practitioner Education. Issue 2 (March 2022) - Knopp, Andrea; Graham, Amy; Stowell, Sarah; Schubert, Carolynn
Abstract: Resource restraints and the movement toward competency-based education encourage exploration of innovative simulation experiences in advanced practice registered nurse education. Building upon existing best practices in simulation development, this pilot project explores opportunities and challenges translating these practices to the advanced practice registered nurse context. Innovations focused on using a competency-based framework, developing a competency-based evaluation tool, and providing feedback from faculty and standardized patients. Lessons learned from this experience inform recommendations for how to design instructional experiences and provide formative methods of feedback for nurse practitioner student assessment.